Soluble Urokinase Plasminogen Activator Receptor Is Associated With Subclinical Myocardial Impairment by Speckle Tracking Echocardiography in Lung Cancer Patients - Manshad, Ahmad S.; Ballout, Fatima A.; Borgia, Jeffrey A.; Reiser, Jochen; Okwuosa, Tochukwu M. (Frontiers in Cardiovascular Medicine, 2022)
Background: Plasma cardiac biomarkers have emerged as a cost-effective diagnostic tool aimed at early identification of cardiotoxicity. Soluble urokinase plasminogen activator receptor (suPAR) is a bone marrow cell derived signaling molecule that is associated with cardiovascular disease outcomes. Objectives: We investigated associations between suPAR and global longitudinal strain (GLS) as a marker of early myocardial impairment in lung cancer patients. Methods: We retrospectively analyzed 52 patients with stage IV non-small cell lung cancer with normal left ventricular ejection fraction (LVEF >55%) and without known heart disease or end-stage renal disease (ESRD). We studied associations between cardiac biomarkers and echocardiographic measures of systolic and diastolic function. GLS was analyzed using 2D speckle-tracking echocardiography via vendor-independent software (TomTec). Results: Median plasma suPAR was 7.0 ng/mL (interquartile range: 5.4-9.0). Mean LVEF was 61.9±8.3% and mean GLS was-19.3±2.1%. Inter-observer reproducibility was excellent for GLS as determined by Intraclass Correlation Coefficient analysis, ICC=0.81 (0.68-0.89). After multivariate analysis, suPAR was the only biomarker associated with GLS (p=0.009). suPAR was also associated with diastolic parameters E velocity (p=0.018), A velocity (p=0.017), and E/E’ ratio (p=0.033). Interestingly, suPAR was not associated with LVEF (p=0.916). In addition, suPAR and GLS were found to be age-independent predictors of all-cause mortality, though only GLS remained significant after multivariate adjustment. Conclusions: In this cohort of stage IV non-small cell lung cancer patients with normal LVEF and without known heart disease or ESRD, suPAR was associated with GLS and diastolic impairment. suPAR may be a readily available cost-effective biomarker of choice in screening for subclinical LV dysfunction in the high-risk oncological population.